AusGeochem: An Open Platform for Geochemical Data Preservation, Dissemination and Synthesis - Boone, S.C.; Dalton, H.; Prent, Alexander; Kohlmann, F.; Theile, M.; Gréau, Y.; Florin, G.; Noble, W.; Hodgekiss, S.A.; Ware, Bryant; Phillips, D.; Kohn, B.; et al. (2022)
To promote a more efficient and transparent geochemistry data ecosystem, a consortium of Australian university research laboratories called the AuScope Geochemistry Network assembled to build a collaborative platform for the express purpose of preserving, disseminating and collating geochronology and isotopic data. In partnership with geoscience-data-solutions company Lithodat Pty Ltd, the open, cloud-based AusGeochem platform (https://ausgeochem.auscope.org.au) was developed to simultaneously serve as a geosample registry, a geochemical data repository and a data analysis tool. Informed by method-specific groups of geochemistry experts and established international data reporting practices, community-agreed database schemas were developed for rock and mineral geosample metadata and secondary ion mass spectrometry U-Pb analysis, with additional models for laser ablation-inductively coupled-mass spectrometry U-Pb and Lu-Hf, Ar-Ar, fission-track and (U-Th-Sm)/He under development. Collectively, the AusGeochem platform provides the geochemistry community with a new, dynamic resource to help facilitate FAIR (Findable, Accessible, Interoperable, Reusable) data management, streamline data dissemination and advanced quantitative investigations of Earth system processes. By systematically archiving detailed geochemical (meta-)data in structured schemas, intractably large datasets comprising thousands of analyses produced by numerous laboratories can be readily interrogated in novel and powerful ways. These include rapid derivation of inter-data relationships, facilitating on-the-fly data compilation, analysis and visualisation.